Clinical outcomes and overview of dedicated venous stents for management of chronic iliocaval and femoral deep venous disease. (April 2022) - Taha, Mohamed AH; Busuttil, Andrew; Bootun, Roshan; Thabet, Bahgat AH; Badawy, Ayman EH; Hassan, Haitham A; Shalhoub, Joseph; Davies, Alun H
Abstract: Objectives: Venous stenting of the lower extremities has grown in popularity and is now considered a key component of the primary treatment strategy for the management of pathologically obstructive or stenotic lesions of the deep venous system. This review aims to provide an overview of the role of venous stenting in the management of chronic conditions affecting the deep venous system of the lower limbs. Methods: An overview of venous stents design and current role of stenting procedure in individuals presenting with Chronic Venous Insufficiency (CVI) and presenting the current trials of dedicated venous stenting in management of chronic deep venous lesions. This review provides a focused insight on venous stent design, physical properties and the available dedicated venous stents selected studies with their related patency outcome based on selective literature search of the PubMed database and Cochrane library. Conclusions: Dedicated venous stent technology is advancing at a rapid pace alongside the increased undertaking of endovascular deep venous stent reconstruction in the management of iliocaval vein pathologies. The ideal design(s) for venous stents remain unknown, although it is hoped that the presence of new dedicated venous stents in clinical practice will allow the generation of experience and data to advance our understanding in this area.